Blue funding of public policies: - Santos, Bruna Barreto Pereira (2023)
More than 70% of Earth's surface is covered by the ocean. It is this ocean that sustains the life and well-being of the entire planet, not only because of the diverse ecosystem that feeds and protects the earth, but also because it serves as a transportation route for most of the goods and services that supply the planet. The way the society organized itself, the ocean became indispensable for the global economy, representing a global social and economic impact. Given this importance, specialists are increasingly alerting to the need for a more sustainable approach to the use of the ocean, in order to minimize the risks in which the ocean is exposed on a daily basis. From this concern was born the idea of the “Blue Economy”. This dissertation researched one specific fund related to the Blue Economy: the EEA Grants. The EEA Grants is a growth program funded by Iceland, Liechtenstein and Norway with the aim of reducing social and economic disparities in Europe. The work was focused on Mário Ruivo Research Vessel and its project specificities. The work analyzed the project from the conception funding until the cost structure of nowadays, when the vessel is operating. In the end of the dissertation, the results were analyzed in order to better understand the profits and losses of the Mário Ruivo Research Vessel project, funded by the EEA Grants.